Growth of Natural Flora during the Fermentation of Inoculated Musts from "Pedro Ximenez" Grapes - Martinez, J.; Millan, C.; Ortega, J.M. (South African Journal of Enology and Viticulture, 2017)
The growth of naturally occurring micro-organisms in musts from grapes collected at three degrees ofripeness (unripe, half· ripe and ripe) in the Montilla-Moriles (Southern Spain) region during 1985and1986 was studied. The musts were inoculated with four physiological races of Saccharomyces cerevisiae isolated in the region. Although the inoculated races of S. cerevisiae prevailed throughout the fermentations, there was also a significant growth of indigenous races of S. cerevisiae and a less marked growth of other micro-organisms such as bacteria, filamentous fungi and yeasts other than S. cerevisiae.